A comparative study of the technical feasibility of complete salpingectomy versus tubal ligation as a method of tubal sterilisation during caesarean delivery - Gupta, Taru; Baruhee, Divya; Agarwal, Sunaina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Recent theory on ovarian malignancy suggests its origin from primary foci in fallopian tubes. Prophylactic salpingectomy may benefit in risk reduction of ovarian cancer. The aim of the study was to compare the feasibility of complete salpingectomy with bilateral tubal ligation was made during caesarean delivery in women desirous of permanent sterilisation. Methods: We conducted a prospective interventional randomized control study in department of obstetrics and gynaecology, ESI-PGIMSR Basaidarapur, New Delhi from October 2018 to February 2021. 70 women participated in this study desiring permanent sterilisation during caesarean delivery. Patients were randomized into two groups who either underwent bilateral tubal ligation [group A (N=35)] or complete bilateral salpingectomy [group B (N=35)]. Results: Procedure was completed in 91% patients in group A and 77% in group B (p >0.05) making both the procedures feasible. Total operative time (min) in group A and B were 47 and 55 respectively (p<0.01). Mean sterilisation procedure time (min) in group A was 5 and group B was 6 (p=0.13). No significant difference was seen in intra-operative blood loss (400 ml in group A vs 300 ml in group B), percentage decrease in post-op haemoglobin (g/dl) (4.56±2.96 in group A vs 3.91±2.7 in group B), post-operative serum Anti-mullerian hormone (AMH) levels (ng/ml) (group A-0.965±0.12 vs 0.7±0.09 in group B) in the two groups. Conclusions: Salpingectomy as an alternative to tubal ligation should be discussed with suitable patients desirous of permanent sterilisation during caesarean delivery.